Analisis Bibliometrik: Tren Penelitian Kemampuan Pemahaman Konsep Matematis Siswa Dalam Pembelajaran Matematika (2019-2024) - Patriani, Putri Nur; Rustika, Putik; Hidayat, Rifqi (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2024)
This research was conducted because it the finding that students had a low ability to understand mathematical concepts.This certainly causes learning obstacles for students. The aim of this bibliometric analysis research is to examine publications related to the field of study with the aim of identifying research trends, important concepts and keywords. This research uses a bibliometric method to collect data with the keywords Mathematical concept comprehension of students in Indefinite Integral material. In light of the results, outcome and conversation, It was discovered that, from 2019 and 2024, 2021 had the most amount of scientific papers on the Google Scholar website.The data collection technique used the Harzing's Publish or Perish program which is available for free and can be accessed. The publications used were released between 2019 and 2024 using VOSviewer which contains 3 views, namely network visualization, overlay visualization, and density visualization. The analysis indicates that this study's results fluctuate annually..Bibliometric results based on terms, the theme regarding Mathematical Concepts Comprehension has a dim color so that there is still little research that examines Indefinite Integral material in particular. Therefore, this can be a reference for further research updates.